EVALUASI KINERJA GURU DAN IMPLIKASINYA TERHADAP PRESTASI BELAJAR PESERTA DIDIK DI MTS AL AMIRIYYAH DARUSSALAM - Wafi Bahrul Ilmi; Fajar Zainulloh; Nico Prasetyo; M Sidiq Purnomo (Hijri, 2025)
The main objective of this study is to analyse the implications of teacher performance evaluation for students' learning achievement at MTs Al-Amiriyyah Darussalam, with an emphasis on the relationship between teachers' pedagogical, professional, and managerial competences and their impact on students' motivation and learning outcomes. This research employs a qualitative approach with a case study design to understand the implications of teacher performance evaluation for students' academic achievement at MTs Al-Amiriyyah Darussalam. The research site and informants were selected purposively, involving teachers, the principal, and students. Data were collected through in-depth interviews, participatory observations, documentation of learning outcomes, and analysis of teacher performance evaluation documents. The data were analysed thematically with data triangulation to ensure credibility. This approach enables a holistic understanding of how teachers' pedagogical, professional, and managerial competences influence students' motivation, engagement, and academic achievement, while taking into account research ethics and data confidentiality.